Persistent Symptoms in Adult Patients 1 Year After Coronavirus Disease 2019 (COVID-19): A Prospective Cohort Study. (5th July 2021) - Seeßle, Jessica; Waterboer, Tim; Hippchen, Theresa; Simon, Julia; Kirchner, Marietta; Lim, Adeline; Müller, Barbara; Merle, Uta
Abstract: Background: Long COVID is defined as the persistence of symptoms beyond 3 months after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. To better understand the long-term course and etiology of symptoms we analyzed a cohort of patients with COVID-19 prospectively. Methods: Patients were included at 5 months after acute COVID-19 in this prospective, noninterventional, follow-up study. Patients followed until 12 months after COVID-19 symptom onset (n = 96; 32.3% hospitalized, 55.2% females) were included in this analysis of symptoms, quality of life (based on an SF-12 survey), laboratory parameters including antinuclear antibodies (ANAs), and SARS-CoV-2 antibody levels. Results: At month 12, only 22.9% of patients were completely free of symptoms and the most frequent symptoms were reduced exercise capacity (56.3%), fatigue (53.1%), dyspnea (37.5%), and problems with concentration (39.6%), finding words (32.3%), and sleeping (26.0%). Females showed significantly more neurocognitive symptoms than males. ANA titers were ≥1:160 in 43.6% of patients at 12 months post–COVID-19 symptom onset, and neurocognitive symptom frequency was significantly higher in the group with an ANA titer ≥1:160 versus <1:160. Compared with patients without symptoms, patients with ≥1 long-COVID symptom at 12 months did not differ significantly with respect to their SARS-CoV-2 antibody levels but had a significantly reduced physical and mental life quality compared with patients without symptoms. Conclusions: Neurocognitive long-COVID symptoms can persist ≥1 year after COVID-19 symptom onset and reduce life quality significantly. Several neurocognitive symptoms were associated with ANA titer elevations. This may indicate autoimmunity as a cofactor in etiology of long COVID. Abstract : Neurocognitive long-COVID symptoms can persist at least for 1 year after acute COVID-19 and reduce life quality significantly. Several neurocognitive symptoms were associated with ANA titer elevations. This may indicate autoimmunity as a cofactor in the etiology of long COVID.